2023
DOI: 10.3389/fendo.2023.1232790
|View full text |Cite
|
Sign up to set email alerts
|

Advances in understanding and treating diabetic kidney disease: focus on tubulointerstitial inflammation mechanisms

Chengren Xu,
Xiaowen Ha,
Shufen Yang
et al.

Abstract: Diabetic kidney disease (DKD) is a serious complication of diabetes that can lead to end-stage kidney disease. Despite its significant impact, most research has concentrated on the glomerulus, with little attention paid to the tubulointerstitial region, which accounts for the majority of the kidney volume. DKD’s tubulointerstitial lesions are characterized by inflammation, fibrosis, and loss of kidney function, and recent studies indicate that these lesions may occur earlier than glomerular lesions. Evidence h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 225 publications
0
8
0
Order By: Relevance
“…IL-1β, IL-6, and TNF-α play vital roles in immune cell regulation, inflammation modulation, and tissue repair in response to injury or infection. In pathological conditions such as kidney diseases, the expression of these inflammatory biomarkers can become dysregulated, leading to an overactive immune response and chronic inflammation. Elevated levels of IL-1β, IL-6, and TNF-α in the kidneys may contribute to tissue damage, fibrosis, and the progression of various kidney disorders, including glomerulonephritis, tubulointerstitial nephritis, and diabetic nephropathy. It is very important to note that monitoring the physiological levels of these inflammatory biomarkers helps in understanding the immune response in kidney pathology and can thus guide therapeutic interventions to mitigate inflammation and prevent further damage . Treatment with HSLF and metformin was able to significantly ( p < 0.05) reverse these harmful increases in pro-inflammatory biomarker levels, suggesting an anti-inflammatory effect of the HSLF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-1β, IL-6, and TNF-α play vital roles in immune cell regulation, inflammation modulation, and tissue repair in response to injury or infection. In pathological conditions such as kidney diseases, the expression of these inflammatory biomarkers can become dysregulated, leading to an overactive immune response and chronic inflammation. Elevated levels of IL-1β, IL-6, and TNF-α in the kidneys may contribute to tissue damage, fibrosis, and the progression of various kidney disorders, including glomerulonephritis, tubulointerstitial nephritis, and diabetic nephropathy. It is very important to note that monitoring the physiological levels of these inflammatory biomarkers helps in understanding the immune response in kidney pathology and can thus guide therapeutic interventions to mitigate inflammation and prevent further damage . Treatment with HSLF and metformin was able to significantly ( p < 0.05) reverse these harmful increases in pro-inflammatory biomarker levels, suggesting an anti-inflammatory effect of the HSLF.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of IL-1β, IL-6, and TNF-α in the kidneys may contribute to tissue damage, fibrosis, and the progression of various kidney disorders, including glomerulonephritis, tubulointerstitial nephritis, and diabetic nephropathy. 58 60 It is very important to note that monitoring the physiological levels of these inflammatory biomarkers helps in understanding the immune response in kidney pathology and can thus guide therapeutic interventions to mitigate inflammation and prevent further damage. 61 Treatment with HSLF and metformin was able to significantly ( p < 0.05) reverse these harmful increases in pro-inflammatory biomarker levels, suggesting an anti-inflammatory effect of the HSLF.…”
Section: Discussionmentioning
confidence: 99%
“…102 Renal tubular structural changes during the development of DKD mainly include tubular cell proliferation and hypertrophy, tubular atrophy, tubular basement membrane thickening, and EMT, leading to interstitial fibrosis. 103 In particular, EMT is the process by which epithelial cells become mesenchymal cells characterised by the absence of epithelial cell markers and the upregulation of the expression of mesenchymal cell markers. 104 Several scholars have reported that DKD-related lncRNAs are associated with renal tubular cell (RTC) injury and mesenchymal fibrosis.…”
Section: Dkd-related Lncrnas Promote Renal Tubular Cell Injury and In...mentioning
confidence: 99%
“…According to recent research, the renal tubules and interstitium also play a very important role in the pathogenesis of DKD, and renal tubular injury occurs in the early stages of DKD and promotes the progression of renal disease 102 . Renal tubular structural changes during the development of DKD mainly include tubular cell proliferation and hypertrophy, tubular atrophy, tubular basement membrane thickening, and EMT, leading to interstitial fibrosis 103 . In particular, EMT is the process by which epithelial cells become mesenchymal cells characterised by the absence of epithelial cell markers and the upregulation of the expression of mesenchymal cell markers 104 .…”
Section: Lncrnas Affect Various Pathologic Changes In Dkdmentioning
confidence: 99%
“…Glomerular hypertension exerts substantial mechanical stress on the capillary walls, being a precursor to glomerulosclerosis and the depletion of peritubular capillaries. Moreover, it facilitates increased protein filtration into the tubular lumen, which triggers the synthesis of proinflammatory and profibrotic factors with accelerated kidney damage [ 31 ].…”
Section: The Role Of Glp-1 Receptor Agonists In Renal Protection and ...mentioning
confidence: 99%